Immunodetection and purification of recombinant human heat shock protein 47 - Fatin Hazwani Ibrahim, 1990-; Mohd. Firdaus Abdul Wahab, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014